2016
DOI: 10.4314/ajtcam.v13i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between total phenolic, total flavonoid and oleuropein in different aged olive (<i>Olea europaea</i> l.) Cultivar leaves

Abstract: Background: Olive leaves have recently gained attention owing to its antioxidant antibacterial, antifungal and anti-inflammatory effects. Bioactive contents of olive leaves differ according to cultivation area, ecological conditions, age of tree, agronomical practices, cultivar, leaf growth stage and other abiotic and biotic stress factors. Material and Method: In this study, Olea europaea L. cultivar (Kilis Yaglık) at different age grown in Kilis were examined. In this context, total phenolic content, total f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…the levels of phenolic compounds were similar between Y and O leaves, which is in agreement with other findings [31]. In fact, it has been found that phenolic contents in different aged olive (Olea europaea L.) cultivar leaves exhibited similar levels [31]. The levels of phenolic compounds in fresh leaves obtained in the present work were slightly lower than the data reported in the literature for Portuguese olive leaf cultivars (i.e.…”
Section: Effect Of Phenolic Compounds On Proliferation Of Human Carcisupporting
confidence: 92%
See 1 more Smart Citation
“…the levels of phenolic compounds were similar between Y and O leaves, which is in agreement with other findings [31]. In fact, it has been found that phenolic contents in different aged olive (Olea europaea L.) cultivar leaves exhibited similar levels [31]. The levels of phenolic compounds in fresh leaves obtained in the present work were slightly lower than the data reported in the literature for Portuguese olive leaf cultivars (i.e.…”
Section: Effect Of Phenolic Compounds On Proliferation Of Human Carcisupporting
confidence: 92%
“…Regarding A549 cell line, the highest cell growth inhibition was 70% for Cobrançosa (Y), followed by Verdeal (Y), Galega (O), Arbequina (O) and Madural (Y) (Figure 8). the levels of phenolic compounds were similar between Y and O leaves, which is in agreement with other findings [31]. In fact, it has been found that phenolic contents in different aged olive (Olea europaea L.) cultivar leaves exhibited similar levels [31].…”
Section: Effect Of Phenolic Compounds On Proliferation Of Human Carcisupporting
confidence: 91%
“…For this reason, a total of ≈1200 samples were collected within 18 classes. Four classes related to olive trees whose spectral differences are influenced by ecological conditions, tree age, agronomic processes, variety, leaf growth rate and other abiotic and biotic stress factors [60].…”
Section: Adding Test Samplesmentioning
confidence: 99%
“…However, the content of phenolics in plants is dynamic and changes according to environmental and developmental conditions [6,9]. In crop plants, phenolics content in leaves somewhat decreases with age, likely because of the decrease in photosynthate supply during leaf maturation [10][11][12][13]. This trend was generally confirmed in tomato, but different phenolic compounds followed different patterns during leaf development and aging [9].…”
Section: Introductionmentioning
confidence: 86%